Dancing with Giants: How Small Women- and Minority-Owned Firms Use Soft Power to Manage Asymmetric Relationships with Larger Partners - Lashley, Kisha; Pollock, Timothy G. (Organization Science, 2020)
We explore how minority- and women-owned suppliers lacking hard power manage asymmetric relationships with larger, more powerful buyers in the context of supplier diversity relationships. We examine how these suppliers create and use soft power to manage the opportunities and challenges they encounter trying to maintain their positions in large buyers’ supply chains. We find that these easily substitutable firms use a variety of information sources to identify and make themselves cognitively central to individuals inside and outside the buyer organizations who can serve as functional and political influencers. They then employ these influencers to affect the buyer’s decisions when their position in the supply chain is threatened, largely without the buyer noticing. Our study contributes to the literatures on the use of soft power buyer-supplier power relationships and supplier diversity.